PRACTICAL SECRETS OF SUCCESSFUL PROFESSIONAL PRESENTATION IN CARDIOLOGY - I. V. Pomortseva (Рациональная фармакотерапия в кардиологии)
Practical secrets of successful professional presentation in cardiology.